Limited Segregation of Different Types of Sound Localization Information among Classes of Units in the Inferior Colliculus - Chase, Steven M. (J Neurosci, 2005)
The auditory system uses three cues to decode sound location: interaural time differences (ITDs), interaural level differences (ILDs), and spectral notches (SNs). Initial processing of these cues is done in separate brainstem nuclei, with ITDs in the medial superior olive, ILDs in the lateral superior olive, and SNs in the dorsal cochlear nucleus. This work addresses the nature of the convergence of localization information in the central nucleus of the inferior colliculus (ICC). Ramachandran et al. (1999) argued that ICC neurons of types V, I, and O, respectively, receive their predominant inputs from ITD-, ILD-, and SN-sensitive brainstem nuclei, suggesting that these ICC response types should be differentially sensitive to localization cues. Here, single-unit responses to simultaneous manipulation of pairs of localization cues were recorded, and the mutual information between discharge rate and individual cues was quantified. Although rate responses to cue variation were generally consistent with those expected from the hypothesized anatomical connections, the differences in information were not as large as expected. Type I units provide the most information, especially about SNs in the physiologically useful range. Type I and O units provide information about ILDs, even at low frequencies at which actual ILDs are very small. ITD information is provided by a subset of all low-frequency neurons. Type V neurons provide information mainly about ITDs and the average binaural intensity. These results are the first to quantify the relative representation of cues in terms of information and suggest a variety of degrees of cue integration in the ICC.